АНАЛІТИЧНИЙ ТА ЧИСЕЛЬНИЙ РОЗРАХУНКИ КВАЗІСТАЦІОНАРНОГО ТРИВИМІРНОГО ЕЛЕКТРОМАГНІТНОГО ПОЛЯ СТРУМОВОГО КОНТУРА ПОБЛИЗУ ЕЛЕКТРОПРОВІДНОГО СЕРЕДОВИЩА - Васецький, Ю.М.; Кучерява, І.М.; Мазуренко, І.Л.; Дзюба, К.К. (Інститут електродинаміки НАН України, Київ, 2022)
The distributions of three-dimensional quasi-stationary electromagnetic field formed in the system of "spatial contour with alternating current – conducting half-space" are analyzed. The calculations are carried out by two ways: analytically and numerically using program Comsol. The obtained data are in agreement with each other. They verify the theoretical result about zero normal components of electric field strength and current density in the conducting half-space. References 3, figures 5.